SMS intervention to improve attendance at the obstetric psychoprophylaxis service in a maternal and child center in Lima, 2020 - Abrigo-Vidal, Fiorella Kiara (2021)
Introduction: Due to the COVID-19 pandemic, various establishments have been offering virtual sessions of obstetric psychoprophylaxis. Like many of the programs in Peru, low adherence requires the implementation of strategies accepted by pregnant women, such as text messages (SMS) that have shown favorable results in other fields. Objective: To evaluate the impact of sending text messages (SMS) as a reminder of appointments in improving attendance at the Obstetric Psychoprophylaxis service. Materials and Methods: Quantitative, true experimental study with a control group. 62 pregnant women who attended the Obstetric Psychoprophylaxis service of the Santa Rosa Maternal and Child Center during the months of October to December 2020 were evaluated, of which 31 received SMS (intervention) and 31 did not (control), the assigned group being a random choice. Attendance at each session was recorded. Additionally, the quality of care was evaluated using SERVQUAL and SERVPERF. The probability of maintaining the sessions over time was evaluated using Hazard Ratio (HR) and Relative Risk (RR). It was approved by the DIRIS Lima Norte and the ethics committee of the Faculty of Medicine of the UNMSM. Results: The analysis showed that having received SMS reduces the risk of stopping attending obstetric psychoprophylaxis sessions (HRa = 0.574; p = 0.047); Likewise, the intervention increases the probability of attending at least 5 (RR = 3.25: p = 0.010) and 6 sessions of the educational program (RR = 4.50; p = 0.020). Finally, the perception of the quality of care was similar in both groups, although in both there was a significant improvement in perception (p <0.05). Conclusions: SMS as a reminder significantly improve attendance at the obstetric psychoprophylaxis service; Likewise, the participants showed an improvement in the perception of the quality of care.